15.0k views
19 votes
How do you figure this out?

How do you figure this out?-example-1
User NeRok
by
4.8k points

2 Answers

9 votes

Answer:

Let the money with Miguel be x.

Then :

Money with Kira = x - 9

Money with Charlie = 4x

Total money in their wallet = $105

This can be written in an equation as :

= \tt \: x + x - 9 + 4x = 105=x+x−9+4x=105

= \tt2x + 4x - 9 = 105=2x+4x−9=105

= \tt 6x - 9 = 105=6x−9=105

= \tt6x = 105 + 9=6x=105+9

= \tt6x = 114=6x=114

= \tt x = \frac{114}{6}=x=

6

114

= \tt x = 19=x=19

Which means :

Money with Miguel = $19

Money with Kira :

= 19 - 9

Thus, Kira has $10 in her wallet.

Money with Charlie :

= 4 × 19

= 76

Thus, Charlie has $76 in his wallet.

Therefore,

Money with Kira = $10

Money with Charlie = $76

Money with Miguel = $19

User Djskinner
by
5.2k points
13 votes

Let the red cat be represented by x.

Let the yellow cat be represented by y.

Let the white cat be represented by z.

Which means :


\tt (1) \: (4)/(5) (20x - 5)


\tt = (4)/(5) * 20x - \frac {4 }{5} * 5


\tt= (80x)/(5) - (20)/(5)


\tt = 16x - 14

Thus, the first statement is correct.


\tt(2) \: (3)/(5) ( (1)/(3) z - 10)


\tt = (3)/(5) * (1)/(3) z - (3)/(5) * 10


\tt = (3)/(15) z- (30)/(5)


\tt = (1)/(5) z - 6

Thus, the second statement is a lie.


\tt(3) \: (1)/(9) ( - 9y - 27x)


\tt= (1)/(9) * - 9y - (1)/(9) * 27x


\tt = ( - 9)/( \: \: 9) y - (27)/(9) x


\tt = (- y) - 3x

Thus, the third statement is correct.

Therefore, the second one is a lie.

User Codingbiz
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.